Blockchain and IoT : foundations, applications and case studies - Anandan, R.; Akila, D.; Pal, Souvik (Chapman & Hall/CRC internet of things., 2025)
This book offers a detailed exploration of the transformative potential of the Internet of Things (IoT) and Blockchain in reshaping industries. Through a combination of theoretical foundations, practical case studies, and innovative applications, it highlights how these cutting-edge technologies can revolutionise business models, enhance operational efficiency, and foster innovation. This is a helpful guide for scholars, researchers, and professionals engaged in research on the Internet of Things, Artificial Intelligence, Machine Learning, Blockchain, and their applications at the industry level. Explains how IoT devices can leverage Blockchain technology to enhance security, transparency, and efficiency in data management and transactions Explores the security challenges faced by IoT devices and how Blockchain can address these challenges by providing a decentralised and tamper-resistant platform for data exchange and storage Investigates the potential of cloud-based IoT platforms, analytics, protocols, and business models and renovate the workforce with Industry revolution Discusses how companies can leverage the data generated by IoT devices securely through Blockchain-based data marketplaces Provides real-world examples and case studies of successful implementations of IoT and Blockchain technologies across different industries such as healthcare, manufacturing, logistics, and energy